セールロンダーネ サンチ ヨビ チョウサ ホウコク 1984 - セールロンダーネ山地予備調査隊; セールロンダーネサンチヨビチョウサタイ; Members of the Sør Rondane Reconnaissance Party (国立極地研究所, 1984)
P(論文) 1984年2月, 第25次南極地域観測隊夏隊と第24次南極地域観測隊越冬隊との合同パーティーによって, セールロンダーネ山地の予備調査が実施された。17日間の調査期間中に測地, 地質, 古地磁気などの地学各分野の予察調査とともに, 将来の観測拠点候補地の選定のための調査をおこなった。調査は4名のスノーモービル隊と6名の雪上車隊の2班構成で進められた。雪上車は分解, 空輸のうえ棚氷上で組み立てられ, スノーモービルは約55km(30マイル)内陸まで空輸された。この空輸拠点(仮称30マイル空輸拠点)には, 今後の調査活動のためにプレハブ小屋を建設し, 帰路に雪上車などの機材をデポした。これらの行動の概要を報告する。 The Japanese Antarctic Research Expedition carried out the reconnaissance survey of the Sør Rondane Mountains (72°S, 25°E) in February 1984. The reconnaissance party consisted of a four-man snowmobile party and a six-man snow vehicle party. The latter party left the Icebreaker SHIRASE in Breid Bay by helicopters on February 7th. Two SM40S-type snow vehicles were knocked down on board, transported by helicopters and set up at about 11km inland from the head of Glacier Bay (provisionally named "L0" point). The snowmobile party was transported 55km inland from the coast ("30 miles point") and started towards the Romnoesfjellet. They arrived at the "Seal" rock on February 11th. The snow vehicle party arrived there on February 13th, after building the prefabricated hut at the "30 miles point" and setting snow stakes along the route from the "L0" point to the Romnoesfjellet via the "30 miles point". During 9 days survey on the northern flank of the Sør Rondane Mountains, they set two geodetic control stations using the JMR satellite positioning system, and carried out geological investigation and collection of rock specimens for the paleomagnetic study. In addition, they conducted the search for the base camp site for the coming season. Both parties were picked up by helicopters at the "30 miles point" on February 23rd after depositing the snow vehicles and other materials. departmental bulletin paper